Safety Training Model for Professional Excellence in Facility Management Practice - Joshua Oluwaseun Lawoyin,; Zamathula Sikhakhane Nwokediegwu,; Ebimor Yinka Gbabo, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Professional excellence in facility management (FM) increasingly depends on the ability of personnel to ensure safe, efficient, and compliant operations across complex facilities. Despite the critical importance of safety, many FM organizations face challenges related to inconsistent training, skill gaps, and insufficient emphasis on behavioral safety culture. This proposes a structured safety training model designed to enhance professional competence in FM, integrating theoretical knowledge, practical skills, and cultural competencies to achieve comprehensive safety performance. The primary purpose of the model is to provide a systematic approach for developing and delivering safety training that aligns with both operational requirements and professional standards. The framework emphasizes the integration of foundational safety principles—including hazard identification, risk assessment, and regulatory compliance—with practical, hands-on skill development tailored to facility-specific operations. In addition, the model incorporates behavioral safety components, focusing on attitude formation, teamwork, communication, and the cultivation of a proactive safety culture. By combining these dimensions, the training model addresses both technical proficiency and human factors, which are essential for reducing workplace incidents and enhancing overall operational resilience. Expected outcomes of implementing the model include improved workplace safety, reduced frequency and severity of incidents, and enhanced adherence to regulatory and organizational standards. Furthermore, by fostering a culture of continuous learning, accountability, and professional development, the model contributes to broader objectives of operational excellence and workforce competency in FM. Organizations can leverage digital platforms, simulations, and blended learning approaches to increase accessibility and engagement, ensuring that safety principles are internalized and applied consistently. Ultimately, this structured safety training model positions facility management as a professional discipline characterized by high standards of safety, operational efficiency, and professional excellence. The model provides a scalable, adaptive, and evidence-based framework that supports both immediate operational safety goals and long-term workforce development, ensuring sustainable improvements in performance and stakeholder confidence.
Keywords: Safety Training; Professional Excellence; Facility Management; Skill Development; Competency Building; Risk Awareness; Compliance Training; Hazard Prevention; Operational Safety; Workforce Preparedness; Continuous Learning; Performance Improvement